2022
DOI: 10.3389/fimmu.2022.939989
|View full text |Cite|
|
Sign up to set email alerts
|

Case report: Persistence of residual antigen and RNA of the SARS-CoV-2 virus in tissues of two patients with long COVID

Abstract: The World Health Organization has defined long COVID-19 (LC) as a condition that occurs in individuals with a history of SARS-CoV-2 infection who exhibit persistent symptoms after its acute phase that last for at least two months and cannot be explained by an alternative diagnosis. Since we had previously reported residual viral antigens in tissues of convalescent patients, we aimed to assess the presence of such antigens in long COVID tissues. Here, we established the presence of the residual virus in the app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…Other putative mechanisms may involve the angiotensinconverting enzyme 2 which is constitutively expressed on the brush border of the small intestinal mucosa and several other gastrointestinal cell types 27 . An emerging body of evidence suggests SARS-CoV-2 liver and other gastrointestinal tissue SARS-CoV-2 tropism, residual viral antigens in gastrointestinal and hepatic tissues, persistence of the virus in gastrointestinal tract reservoirs, and ongoing viral replication in the appendix in the post-acute phase of the disease and alteration of gut microbiota in people with Long Covid 30,34,[38][39][40][41][42][43] . Studies integrating multi-dimensional immune phenotyping and machine learning suggested that compared to matched controls, people with Long Covid had increased levels of humoral responses directed against SARS-CoV-2, elevated antibody responses directed against Epstein-Barr virus and elevated cortisol levels but not autoantibodies to human exoproteomealtogether suggesting that persistent antigen, reactivation of latent herpesviruses, and chronic inflammation may be key mechanisms for Long Covid 33 .…”
Section: Signs and Symptomsmentioning
confidence: 99%
“…Other putative mechanisms may involve the angiotensinconverting enzyme 2 which is constitutively expressed on the brush border of the small intestinal mucosa and several other gastrointestinal cell types 27 . An emerging body of evidence suggests SARS-CoV-2 liver and other gastrointestinal tissue SARS-CoV-2 tropism, residual viral antigens in gastrointestinal and hepatic tissues, persistence of the virus in gastrointestinal tract reservoirs, and ongoing viral replication in the appendix in the post-acute phase of the disease and alteration of gut microbiota in people with Long Covid 30,34,[38][39][40][41][42][43] . Studies integrating multi-dimensional immune phenotyping and machine learning suggested that compared to matched controls, people with Long Covid had increased levels of humoral responses directed against SARS-CoV-2, elevated antibody responses directed against Epstein-Barr virus and elevated cortisol levels but not autoantibodies to human exoproteomealtogether suggesting that persistent antigen, reactivation of latent herpesviruses, and chronic inflammation may be key mechanisms for Long Covid 33 .…”
Section: Signs and Symptomsmentioning
confidence: 99%
“…Heading toward a Pan-SARS-CoV-2 vaccine Of additional clinical interest with strong T cell immunity is its function of viral clearance. Persistent SARS-CoV-2 infections can contribute to long COVID as residual viable SARS--CoV-2 particles, viral replication, viral RNA and viral spike protein antigens could sustain in tissues of the convalescents [81][82][83]. As long COVID is found to be associated with a decline in IFN-γ-producing CD8 + T cell [84], enhancing T cell immunity for clearance of residual systemic infection (sustained viral reservoirs) could be a sensible strategy for prevention of long COVID.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Goh et al [ 69 ] also reported two cases of LC with persistent viral antigens and/or RNA. The first case had residual virus cells in both gastrointestinal and non-gastrointestinal tissue for up to 426 days, while the second case had residual virus cells in non-gastrointestinal tissue.…”
Section: Chronic Virus Infection Residual Virus Proteins and Cancer Riskmentioning
confidence: 99%